ANALISIS BEBERAPA PARAMETER KUALITAS MINYAK PADA KOPRA DAN BUNGKIL KELAPA - Rorong, Johnly (CHEMISTRY PROGRESS, 2009)
A research was done to analyses oil quality in copra and coconut waste using some methods such aswater content, % Residual Oil Content. Base on results, data was obtained: water content (coconut waste)was 1.610%, Flakes Flakes value 8.322 and Conditioner Flakes value 1.612. water content for copra was6.785%, coconut waste (D.B) was 11.123% with Cooker Flakes value 2.112. Analyses of % Oil Contentcopra (dry basis, oven) was 65.329%, % Oil Content of copra (dry basis, oven) was 70.083%. Resultshows that persentase Oil Content copra at wet basis already agree to standard that is 65-66%.Persentase (%) RO coconut waste at wet basis (oven) already agree to standard that is < 10.00 %Â Keywords : copra, coconut waste, residual oil content